2013
DOI: 10.1590/s2317-64312013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Oficinas educativas como estratégia de promoção da saúde auditiva do adolescente: estudo exploratório

Abstract: Purpose: Develop and evaluate educational workshop on hearing health and noise exposure adolescents, students of public school. Methods: Intervention study involving 91 adolescents. Educational activity was conduce based on the problem-posing education and as a methodological resource group work in the form of workshops in which young people were invited to reflect on the hearing health and noise exposure in cultural activities (leisure),and environmental education. Was used differents strategies playful and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 11 publications
1
10
0
19
Order By: Relevance
“…In the present study, as in previous ones, we observed that most adolescents used earphones (1,7,12,22) . These findings show the importance of educational/ preventive actions to help improve the awareness of adolescents to exposure to high-intensity music, as suggested in the literature (2,8,14,15,19,21,23) . Some initiatives have already been developed for the purpose of promoting and protecting the auditory health of school students.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In the present study, as in previous ones, we observed that most adolescents used earphones (1,7,12,22) . These findings show the importance of educational/ preventive actions to help improve the awareness of adolescents to exposure to high-intensity music, as suggested in the literature (2,8,14,15,19,21,23) . Some initiatives have already been developed for the purpose of promoting and protecting the auditory health of school students.…”
Section: Discussionsupporting
confidence: 65%
“…However, after the educational lecture, it was possible to observe a significant habit change among a few adolescents (Table 3) who began to set the average intensity of the equipment as the limit. Inadequate attitudes related to auditory health and consequences of noise may be caused by lack of information and absence of interesting educational activities targeting this population, among other reasons (21) . The findings showed that most adolescents remained exposed to high-intensity music, using earphones for fewer than 3 hours a day (Table 3), a fact that was also found in other studies (3,7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teenagers, according to recent studies, have demonstrated harmful habits and behavior considered as improper to hearing health 19 . Such habits are explained in relation to adolescence concepts and usual association with high music 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Estudos mostram esta relação entre o aumento das patologias em função dos hábitos nocivos frequentes nesta faixa etária 19 .…”
Section: Discussionunclassified